A numerical analysis of slab heating characteristics in a rolling type reheating furnace with pulse combustion. (25th August 2016) - Liu, Y.J.; Li, J.D.; Misra, R.D.K.; Wang, Z.D.; Wang, G.D.
Highlights: A three-dimensional unsteady model for rolling type reheating furnace has been developed. The gas velocity distribution and motion characteristics were obtained. The influence on temperature distribution of slab was studied. Simulation results were consistent with experimental. Abstract: Numerical analysis of slab heating characteristics in a reheating furnace was accomplished using fluid dynamics software FLUENT. The complicated geometry of the mesh using finite volume method (FVM) simulation was built based on the practical aspects of the reheat furnace. The effect of slab of flow field and temperature distribution inside the furnace on heating efficiency and uniformity in heating was studied. The phenomena in the furnace were periodically transient when slabs were heated with controlled time interval. A user-defined function (UDF) program was developed to process the sequence pulse combustion because FLUENT cannot handle the movement using its default functions. The numerical results were in good agreement with the corresponding experimental data. In order to improve the heating efficiency, the heating precision and the temperature uniformity of the medium and heavy slab, a basic model is proposed. The study is directly applicable in optimizing the process.